A rare case of conjoined twins: craniothoraco omphalopagus-non janiceps - Devi, L. Thulasi; Prasad, Gurusamy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
A very rare case of conjoined twins, incompatible with life. Craniothoraco omphalopagus terminated after second trimester anomalies scan. Only anecdotal case reports were available and their inheritance pattern remains a mystery. They were inoperable. Here we present such a case which was unbooked and unregistered and escaped detection till late second trimester due to non-availability of maternity services. These cases if they reached term had to be delivered always by classical caesarean due to obstructed labour and difficulty in delivery via LUS due to variety of difficulties and manoeuvrability by obstetrician. LSCS should not be attempted as it invariably leads to an inverted T scar on the uterus with increased blood loss. A classical caesarean section always leads to increased risk of future rupture and spoils the obstetric career of the woman. These cases if detected early can be delivered vaginally with ease by an experienced consultant.